Tourism strategies and local responses in Southern Africa - Hottola, Petri (CABI, 2009)
This book discusses tourism development in Namibia. It consists of 12 major chapters. Chapter 2 explores the opportunities and challenges of implementing a national tourism policy in Namibia, as perceived by tourism entrepreneurs. Chapter 3 presents the South African experiences for local economic development (LED) in rural route tourism, also a potentially strategic tool for development through tourism in the rest of Southern Africa. Chapter 4 discusses the modernization approach to tourism development, both in theory and practice. Chapter 5 discusses their commoditization in the Namibian tourism promotion, thereby defining their symbolic role in Namibian tourism development policies.